DIETARY INTAKE AND PREVALENCE OF ADOLESCENT HYPERTENSIVE IN PORT HARCOURT, NIGERIA - G. O., Wordu; Chikodi H. I., Wachukwu (International Journal of Research -GRANTHAALAYAH, 2019)
Hypertension is the commonest non communicable disease affecting both adolescents and adults. Its origin is in childhood, but information on its prevalence and associated risk factors in adolescents are scarce. This study assessed the prevalence of High blood pressure and associated risk factors on an adolescents in Port Harcourt, Nigeria. A cross-sectional descriptive study of 150 respondents selected using a multistage sampling technique from secondary schools in Port Harcourt. Height, weight and blood pressure (BP) of the respondents were measured, while body mass index (BMI) were calculated using standard methods. Hypertension, overweight and obesity were recorded high among participants. About 22%, 28.8% and 34.7% were in the categories of prehypertension, stage by hypertension and stage 2 hypertension respectively. A total of 36.16% were overweight and 9.3% obsessed. This study demonstrated high prevalence of hypertension overweight and obesity among the adolescents in Port Harcourt other intervention to promote healthy eating habits and life styles, especially among high risk groups are suggested. Similar studies should be conducted in a rural setting.